2019
DOI: 10.11114/afa.v5i2.4410
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Working Capital Management and Financial Sustainability of Selected Christian Denominations in Ghana

Abstract: Management of working capital is a fundamental aspect of finance. This is because it affects the church's liquidity and financial sustainability. The study sort of establishing the relationship between working capital and financial sustainability for selected Christian denominations in Ghana. Using bivariate correlation application in SPSS 23, the financial statements from 2013 to 2017 of 15 Christian Council of Ghana denominational members conveniently sampled and analyzed. Working capital is represented by l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…In another Sub-Saharan African country, Ghana, a study by Peprah and Riziki (2019) found that there was a small but significant negative relationship between working capital management and profitability, while Yeboah and Yeboah (2014) concluded that although some components of working capital management such as cash conversion cycle and payables payment period had a statistically significant relationship with profitability, the receivables collection period did not. Similarly, although the cash operating cycle and receivables collection period had a significantly positive relationship with bank profitability, the payables payment period exhibited a significantly opposite relationship with profitability (Agyei and Yeboah, 2011).…”
Section: Literature Surveymentioning
confidence: 99%
“…In another Sub-Saharan African country, Ghana, a study by Peprah and Riziki (2019) found that there was a small but significant negative relationship between working capital management and profitability, while Yeboah and Yeboah (2014) concluded that although some components of working capital management such as cash conversion cycle and payables payment period had a statistically significant relationship with profitability, the receivables collection period did not. Similarly, although the cash operating cycle and receivables collection period had a significantly positive relationship with bank profitability, the payables payment period exhibited a significantly opposite relationship with profitability (Agyei and Yeboah, 2011).…”
Section: Literature Surveymentioning
confidence: 99%